Soft Skills: Important Skills for Teachers in Multicultural Society - Chaiyapan, Maithai; Suksawat, Jirasuk (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
Teachers play an important role in the development of students’ learning and in motivating them to achieve academic, professional, personal, and social success. Soft skills, which are a set of intra-personal and interpersonal skills related to abilities, behaviors, and attitudes that help teachers adapt working with others and adjust themselves with surroundings. Soft skills can also promote the development of other skills, such as academic, technical, and professional skills. In particular, teachers working in multicultural society must have broader vision, positive attitude and recognize cultural diversity in classroom. Teachers should be familiar with a diverse classroom and enhance students working together in harmony in the diverse classroom. As a result, soft skills are similar to a career supporter for teachers who know students, admire diversity, and are aware of the dynamic link between the things surrounding the learner. This article aimed to present soft skills-related issues in order to create more understanding of these skills, comprising of 3 dimensions: Teacher competencies in multicultural society, Soft skills for teachers affecting learners and Soft skills development for teachers in multicultural society. These guidelines will be an important mechanism in promoting the development of teachers to be truly successful in life and work.